A force controlled tribometer for pre-sliding measurements at the nanometer scale - Du, Junxiao; Franklin, Steve; Weber, Bart (Frontiers in Mechanical Engineering, 2023)
In the pre-sliding friction regime, interfaces partially stick and partially slip. The pre-slip is thought to be locally initiated at regions of the interface where the ratio of shear stress to normal stress exceeds a critical value. The displacements involved in pre-slip can be limited to the nanoscale, especially for stiff interfaces. Furthermore, little is known experimentally about the interplay between surface topography, pre-sliding behavior and wear. In this work, we introduce a pre-sliding tribometer that enables the study of how the pre-sliding friction at various types of ball-on-flat interfaces evolves as a function of wear. Polytetrafluoroethylene-on-silicon (PTFE-on-Si) pre-sliding measurements covering interfacial displacements up to 50 nanometers, conducted with the new instrument, show good agreement with Mindlin theory predictions, without adjustable parameters.